Direct costs associated with the appropriateness of hospital stay in elderly population - Sánchez-García Sergio; Morales-Cisneros Gabriela; Espinel-Bermúdez Claudia; Juárez-Cedillo Teresa; Contreras-Hernández Iris; García-Peña Carmen; Mould-Quevedo Joaquín F (BMC, 2009)
Abstract Background Ageing of Mexican population implies greater demand of hospital services. Nevertheless, the available resources are used inadequately. In this study, the direct medical costs associated with the appropriateness of elderly populations hospital stay are estimated. Methods Appropriateness of hospital stay was evaluated with the Appropriateness Evaluation Protocol (AEP). Direct medical costs associated with hospital stay under the third-party payer's institutional perspective were estimated, using as information source the clinical files of 60 years of age and older patients, hospitalized during year 2004 in a Regional Hospital from the Mexican Social Security Institute (IMSS), in Mexico City. Results The sample consisted of 724 clinical files, with a mean of 5.3 days (95% CI = 4.9-5.8) of hospital stay, of which 12.4% (n = 90) were classified with at least one inappropriate patient day, with a mean of 2.2 days (95% CI = 1.6 - 2.7). The main cause of inappropriateness days was the inexistence of a diagnostic and/or treatment plan, 98.9% (n = 89). The mean cost for an appropriate hospitalization per patient resulted in US$1,497.2 (95% CI = US$323.2 - US$4,931.4), while the corresponding mean cost for an inappropriate hospitalization per patient resulted in US$2,323.3 (95% CI = US$471.7 - US$6,198.3), (p < 0.001). Conclusion Elderly patients who were inappropriately hospitalized had a higher rate of inappropriate patient days. The average of inappropriate patient days cost is considerably higher than appropriate days. In this study, inappropriate hospital-stay causes could be attributable to physicians and current organizational management.